Development of a database for efficient management of gas stations - Gulnara A. Gareeva; Aigul G. Faizullina; Zulfina Sh. Aglyamova; Yulia N. Burkhanova; Ruslan V. Spevakov (International Journal of Advanced Studies)
Background. Modern gasoline stations face a number of challenges related to data management, inventory accounting, and customer service. Traditional accounting and management methods are often inefficient, resulting in increased time spent on processing information and an increased likelihood of errors. The lack of a centralized system for storing and processing data makes it difficult to analyze sales and manage inventory, which negatively affects the overall efficiency of the station.